(untitled) (Dhaka University Journal of Science, 2013)
Beet Pectin (SBP) polysaccharide. Aqueous solution properties of these samples have been studied using Ubbelohde capillary viscometer in the dilute regime. Intrinsic viscosity [?] was estimated for different SBP solution samples prepared from heat-treated SBP powdered samples with different heating time. Results suggest that heat treatment has a significant effect on solution behavior of SBP samples. Intrinsic viscosities decreased with increasing heating time indicating that heat-treated SBP molecules are compact than the untreated one and the compactness increases with increasing heating time at 80°C. The intrinsic viscosities of these samples were plotted as a function of the corresponding molecular weight of the samples and can be expressed by a power law. The power law exponent was estimated as 1.4 indicating that pectin molecules takes the conformation of stiff polymer chains in dilute solution. Dhaka Univ. J. Sci. 61(1): 117-123, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15107